2007
DOI: 10.1063/1.2718485
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of the dynamical behaviors of an aromatic carboxylic acid molecule with different conformations on a Au (111) surface

Abstract: In this study, the behavior of a single tricarboxylic acid derivative, 1,3,5-tris͑carboxymethoxy͒ benzene ͓TCMB, C 6 H 3 ͑OCH 2 COOH͒ 3 ͔ on a Au ͑111͒ substrate at 50 K has been investigated by molecular dynamics simulation. Four possible conformations of the TCMB molecule adsorbed on the Au ͑111͒ substrate are found and which display different trajectories of movement and dynamical behaviors. The lock-and-key geometry between the TCMB molecule of different conformations and atomic arrangement of the Au ͑111͒… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
5
9
0
Order By: Relevance
“…(9) and the potential of the substrate Eq. (10), which is at least two orders of magnitude smaller, it can be concluded that the right-hand sides of Eqs. (20) and (21) are at least two orders of magnitude larger than the right-hand side of Eq.…”
Section: Effective Interactionmentioning
confidence: 92%
See 2 more Smart Citations
“…(9) and the potential of the substrate Eq. (10), which is at least two orders of magnitude smaller, it can be concluded that the right-hand sides of Eqs. (20) and (21) are at least two orders of magnitude larger than the right-hand side of Eq.…”
Section: Effective Interactionmentioning
confidence: 92%
“…The internal configuration of the molecules affects the interaction with the substrate and therefore transport (see, for instance, Refs. [9,10]). However, the deterministic internal DOF can also act as a source of noise [5,11] if their dynamics are sufficiently fast and chaotic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of diffusion of large molecules adsorbed on a surface, the internal dynamics of the molecules can be such a source of noise. Experimental [30] and numerical [16] evidence exists demonstrating that rotational and other internal degrees of freedom affect the diffusion. In some cases clusters of molecules have been shown to diffuse more rapidly than single particles [8,25].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study 41 used MD simulation to investigate the dynamic behavior of 1,3,5-triscarboxymethoxy benzene (TCMB, C 6 H 3 (OCH 2 COOH) 3 on an Au(111) substrate at a temperature of 50 K. This study determined that, when LAK geometry appeared between the aromatic ring and Au(111) surface atom, the TCMB molecule resided atop the Au atom for 1.1-1.3 ns, which is significantly longer than for other orientations of the TCMB on the Au(111). In addition, for S7 and PF8 on Au (111), the local Phe-Pro pair LAK structures were predicted to extend the time that S7 and PF8 remained stably on the Au(111) facet, enhancing the growth of the (111) facet for AuNP.…”
Section: )(Right) As Shown Inmentioning
confidence: 98%